A Preliminary Multimethod Comparison of Sleep Among Adolescents With and Without Generalized Anxiety Disorder. Issue 2 (4th March 2017) - Mullin, Benjamin C.; Pyle, Laura; Haraden, Dustin; Riederer, Justin; Brim, Natalie; Kaplan, David; Novins, Douglas
Abstract : Previous studies suggest that youth with anxiety disorders experience their sleep as more disrupted and unsatisfying than their healthy peers. However, it is unclear whether these subjective complaints align with objective measures of sleep quantity and quality. The purpose of this preliminary study was to assess subjective and objective sleep parameters, and their relationships with anxiety symptomatology, among adolescents (62.8% female, 81.4% Caucasian), ages 12 to 18 ( M  = 15.29 years), with generalized anxiety disorder ( n  = 26) and controls without any psychopathology ( n  = 17). We measured sleep over 7 nights using sleep diaries and actigraphy and collected self- and parent-report questionnaires pertaining to sleep, anxiety, and depression. Repeated-measures mixed models were used to examine relationships between nightly sleep duration and morning anxiety. We found a number of differences in sleep between our anxious and healthy participants. Via sleep diary, our anxious participants had longer sleep onset latencies and lower satisfaction with sleep relative to controls, whereas via actigraphy we found longer sleep onset latencies but greater overall sleep duration among anxious versus control participants. Actigraphic measures of sleep disturbance were associated with parent-report of anxiety and depression. Our mixed-model analyses revealed that decreases in nightly sleep duration were associated with increased morning anxiety, but only among our participants with generalized anxiety disorder. Findings suggest that sleep disturbance among anxious adolescents can be detected using both subjective and objective measures and that, for these individuals, fluctuations in sleep duration may have real consequences for daytime anxiety.